Transient Modelling of Permafrost Distribution in Iceland - Czekirda, Justyna; Westermann, Sebastian; Etzelmüller, Bernd; Jóhannesson, Tómas (Frontiers in Earth Science, 2019)
Warming and degradation of permafrost during the ongoing climate change is of growing concern. Recently, permafrost thawing has been recognized as a new factor triggering landslides in Iceland. Therefore, there is an increased need for a more thorough understanding of permafrost distribution and the temporal evolution of the ground thermal regime in this region. This study focuses on regional modelling of ground temperature evolution in Iceland for the last six decades (1960–2016) by employing the transient permafrost model CryoGrid 2 at 1-km spatial resolution. To account for the strong wind redistribution of snow in Iceland, we ran three realizations of the model, by forcing the embodied snow water equivalent model with 50 %, 100 % and 150 % of gridded precipitation. The modelled permafrost extent strongly depends on snow depth, with around three to fifteen times more cells indicating permafrost in the halved-precipitation run in comparison to the other two precipitation runs. A three- to four-decade-long warming trend has led to warming or degradation of permafrost in some areas of Iceland. We roughly estimate that ~11 % and ~7 % of the land area of Iceland was underlain by permafrost during the periods 1980–1989 and 2010–2016, respectively. Model validation with ground temperature measurements and the distribution of permafrost-related landforms, such as active rock glaciers and stable ice-cored moraines, together with palsas and peat plateaus, shows good agreement. The simulation results may be further used as a baseline for modelling of future permafrost evolution at a regional scale or for identification of landslide-susceptible areas in Iceland.